Obtención de una pomada a base de extracto natural de Guatila destinada al uso fitoterapéutico (2019)
Guatila is a little-known cucurbitaceae that currently is destined, for the most part, to the feeding of livestock species, which makes it a despised specie despite its multiple properties. This degree work is based on the development of an ointment based on natural extract of guatila, intended for use in the phytotherapy field, in order to exploit one of the many properties of this fruit, related to its antifungal, antibacterial and anti-inflammatory capacity. This research includes the sequential development of different stages, ranging from the collection and analysis of theoretical data to experimentation at the laboratory level and the processing of results, which allow the appropriate selection of the best method to obtain the guatila extract and the establishment of the optimal conditions for the production of the phytotherapeutic preparation, considering the main factors of each unit operation involved and the use of natural components. Qualitative and quantitative analyzes of the raw materials and the final product are considered, among which the quantification of flavonoids, as the active principle of the ointment, responsible for granting the product healing properties, stands out. On the other hand, and by using the results at the laboratory scale, the process conditions were established at the pilot plant level and subsequently the most suitable equipment were selected and sized for the main stages. EduleCare ointment was also evaluated through the execution of an acceptance panel, whose results show the approval of the public and directly guarantee the quality of the product.